Objective Comparison of Animal Training Versus Artificial Simulation for Initial Cricothyroidotomy Training. Issue 5 (May 2015) - Iverson, Kyle; Riojas, Ramon; Sharon, Danny; Hall, Andrew B.
This manuscript aims to determine if there is a difference in performance outcomes after initial training with either animals or simulators. Volunteers without prior experience performing emergency procedures were randomly assigned to receive training in cricothyroidotomy on either a pig model or on an artificial simulator. Volunteers were given identical lectures and trained to proficiency. Two weeks after training, trainees were tested using human cadavers as to their performance with time, incision size, incision start location, initial placement attempt, and final accuracy. Overall success rate of the animal-trained group was 64 per cent and in the artificial simulator group, 73 per cent ( P = 0.431). Median time to completion in the animal group and artificial simulator group was 143 s and 105 s ( P = 0.482), and incision lengths 4.0 cm and 3.2 cm ( P = 0.173), respectively. Accuracy of initially attempted incision placement and final cricothyroidotomy tube placement was also compared. Initially attempted site accuracy in the animal-trained group was 93 per cent and correct final position 79 per cent, and in the artificial group, 100 per cent ( P = 0.452) and 88 per cent ( P = 0.782), respectively. There was no statistically significant, objective difference in any metric between animal- and simulator-trained groups after cricothyroidotomy training. For initial training, there is no objective benefit of animal training.